KEPEMIMPINAN INOVATIF KEPALA DAERAH DI ERA PANDEMI COVID-19 : STUDI KASUS WALIKOTA SEMARANG, HENDRAR PRIHADI. - Ode, Samsul (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
Leadership is an important aspect of governance. The role of a leader is needed in order to solve various problems that occur in society. Determination of the status of the Covid-19 pandemic at the global, regional and national to local levels brings with it a number of problems faced by local governments. Semarang City is one of the cities that is facing the impacts that occur due to the determination of the Covid-19 pandemic status. Hendrar Prihadi, as the mayor of Semarang, has made policies and innovations in order to respond to problems that occur in society due to the outbreak of the corona virus. The results showed that the innovative leadership style adopted by Hendrar Prihadi was able to overcome the problems faced by the community and local government of the city of Semarang. The various appreciations and awards received by the Semarang city government are proof that Hendrar Prihadi's innovative leadership style has a good role in managing governance in the city of Semarang during the Covid-19 pandemic. Keywords: Innovative Leadership, Covid-19, Hendrar Prihadi, Semarang City